Business strategy for Synthetic Peptides from Leiurus quinquestriatus Scorpion in the Indonesian Market - Nugraha, Ilham Wira; Herlina, Sri (Journal of Business Management Education (JBME), 2025)
The purpose of this study is to examine the business plan for creating synthetic peptides from the Leiurus quinquestriatusscorpion for the Indonesian market. This study analyzes critical elements that impact product success through internal and external analysis and the application of analytical methodologies including SWOT. According to the study's findings, the company's primary obstacles are stringent rules and scarce resources, despite its advantages in technology and raw material potential. The growing demand in the cosmetics and pharmaceutical industries presents excellent potential. To overcome obstacles and seize market possibilities, the suggested tactics include product differentiation, enhancing production capacity, and working with regulatory bodies and academic institutions.